Breaking the sound barrier: towards next-generation AAV vectors for gene therapy of hearing disorders - Fakhiri, Julia; Landegger, Lukas; Grimm, Dirk (Hearing research, 2022)
Owing to the advances in transgenic animal technology and the advent of the next-generation sequencing era, over 120 genes causing hereditary hearing loss have been identified by now. In parallel, the field of human gene therapy continues to make exciting and rapid progress, culminating in the recent approval of several ex vivo and in vivo applications. Despite these encouraging developments and the growing interest in causative treatments for hearing disorders, gene therapeutic interventions in the inner ear remain in their infancy and await clinical translation. This review focuses on the adeno-associated virus (AAV), which nowadays represents one of the safest and most promising vectors in gene therapy. We first provide an overview of AAV biology and outline the principles of therapeutic gene transfer with recombinant AAV vectors, before pointing out major challenges and solutions for clinical translation including vector manufacturing and species translatability. Finally, we highlight seminal technologies for engineering and selection of next-generation "designer" AAV capsids, and illustrate their power and potential with recent examples of their application for inner ear gene transfer in animals.